Jorrit Tornquist - Il progetto cromatico della torre del Termoutilizzatore di Brescia - Zambelli, Matteo (Firenze Architettura, 2017)
The tower of the waste-to-energy plant in Brescia raises some questions: the use of colour for creating perceptive and chromatic effects at the scale of the architectural object, but with an impact also at the territorial scale, the theme of ascribing new meanings to merely functional elements, yet with a strong architectural impact, and finally the theme of “archisculpture”, that is of architecture which becomes sculpture.